2019
DOI: 10.1111/trf.15520
|View full text |Cite
|
Sign up to set email alerts
|

Performance and reliability of a benchtop automated instrument for transfusion testing: a comparative multicenter clinical study in the US population

Abstract: BACKGROUND: Heavy workload in hospital transfusion services and blood centers necessitates the implementation of automated platforms. We evaluated the performance of Erytra Eflexis (Diagnostic Grifols), a recently developed midsize automated instrument for pretransfusion testing, in comparison with a US Food and Drug Administration (FDA)-cleared device (Erytra). Reproducibility and repeatability of the results were also investigated.STUDY DESIGN AND METHODS: Studies were conducted using the same card technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…ABO group testing is highly important, labeling with an incorrect blood grouping could lead to a hypothetical risk of an incompatible transfusion with significant clinical consequences. ABO discrepant rates observed for commercially available platforms or techniques are 0.16% 6 or above. [7][8][9] During this study, the microarray-based system showed a 100% concordance rate for ABO after software re-parametrization.…”
Section: Discussionmentioning
confidence: 94%
“…ABO group testing is highly important, labeling with an incorrect blood grouping could lead to a hypothetical risk of an incompatible transfusion with significant clinical consequences. ABO discrepant rates observed for commercially available platforms or techniques are 0.16% 6 or above. [7][8][9] During this study, the microarray-based system showed a 100% concordance rate for ABO after software re-parametrization.…”
Section: Discussionmentioning
confidence: 94%
“…아주대병 원은 2020년 1월 말에 이 장비를 도입하여 국내 대 학병원으로서는 처음으로 사용하고 있다 [1]. 이 장 비는 혈액형 검사, 비예기항체 선별 및 동정검사 및 교차시험용으로 통상적으로 이용되고 있다 [2,3].…”
Section: 서 론unclassified
“…Other facilities such as blood banks, transfusion centers, and biobanks cannot operate without carefully setting and executing policies for the large-scale storage of the accumulated blood and cell samples [10][11][12]. From a technical viewpoint, this needs specialized devices that are capable of achieving and maintaining a desired temperature level with a very high degree of accuracy, reliability, and traceability [13,14]. As a rule, medical care facilities set appropriate policies and standards for the operation of these devices within the framework imposed by government regulatory agencies, but they do not have the necessary technical expertise to design and develop the devices themselves [15][16][17].…”
Section: Introductionmentioning
confidence: 99%